2021
DOI: 10.1097/ypg.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Co-existing bipolar disease and 17q12 deletion: a rare case report

Abstract: Background 17q12 microdeletion syndrome is a rare autosomal dominant chromosomal anomaly, caused by the deletion of a 1.4 Mb-spanning DNA sequence on the long arm of chromosome 17. Herein, we report the first bipolar disease (BPD) case with a 1.6-Mb deletion in the 17q11.2-17q12 chromosome region. Materials and methodsPhysical examination of the case was performed. Karyotype and microarray analyses were performed for the case and the parents. ResultsPhysical examination revealed mild dysmorphic features such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Several studies reported on patients with HNF1B variations in single case studies or case series. Considerably more case studies on patients with a 17q12 microdeletion ( 41 , 42 , 44 46 , 48 50 , 54 , 58 , 60 ) have been published than on patients with a mutation of HNF1B ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported on patients with HNF1B variations in single case studies or case series. Considerably more case studies on patients with a 17q12 microdeletion ( 41 , 42 , 44 46 , 48 50 , 54 , 58 , 60 ) have been published than on patients with a mutation of HNF1B ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the single case studies, all patients with a 17q12 microdeletion were reported to have some kind of NDD, including intellectual disability ( 41 , 44 , 48 ), ADHD ( 48 , 58 ), or ASD ( 49 ). The patient in the single case study with a mutation of HNF1B was reported to have a learning disorder ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although phenotypic variations are seen in individuals with the 17q12 microdeletion, classical manifestations include diabetes, renal and genitourinary abnormalities, and neuropsychiatric and neurodevelopmental disorders 1,2 . Specifically, this microdeletion confers an increased risk for anxiety disorders, autism spectrum disorder (ASD), bipolar disorder, and schizophrenia 2–5 …”
mentioning
confidence: 99%